Analysing the National Systems of Innovation in ACP Countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
At the beginning of the year, CTA initiated collaboration with the United Nations University/Institute of Technologies (UNU/INTECH) to develop a methodological framework for analysing the national agricultural science, technology and innovation system (AS